Implementation of Driver Medical Check-Up Web-Based Application at Clinic PT. XYZ Indonesia - Yapanto, Maura DM (IT for Society, 2024)
The Clinic at PT XYZ Indonesia consistently implements Medical Check-Up for all workers, especially the drivers in charge of picking up employees. After carrying out the medical check-up driver process, the admin in managing and compiling patient data reports still uses a manual system. This causes delays in delivering information and reporting daily patient data. The purpose of this final project is to develop a web-based application that can make it easier for admin to carry out medical check-ups for drivers. This Final Project will be developed using the Rapid Application Development (RAD) method. Under these conditions, this web-based application for driver medical check-up will be developed using PHP 7 and MySQL database. This web-based application driver medical check- up will be equipped with several features, there are login, dashboards, doctors, patients, rooms, blood pressure, view medical records and download reports from medical records.